A review on interferometry lightning mapping system and its deployment in Palembang Indonesia - Oktaviani, Wiwin A.; Sidik, Muhammad Abu Bakar; Ahmad, Mohd. Riduan; Jambak, Muhammad Irfan (Institute of Advanced Engineering and Science, 2024)
Climate change effects influence the sustainability of wind and photovoltaic energies as renewable sources. Similarly, infrastructure for renewable energy is structurally vulnerable to lightning strikes. Hence, a system for detecting and monitoring lightning activity is necessary to predict and adapt to climate change trends and to enhance the lightning protection system's capability. One such system for observing and locating lightning is very high frequency (VHF) interferometry. Various factors, such as the baseline distance between sensors, the frequencies used, and the quality of the analyzed signal, will influence the system's accuracy. This paper discusses these factors through an extensive literature review. This study aims to identify the factor that most significantly affects the system's accuracy and to determine the technical adjustments required to improve this accuracy. Enhanced precision in the interferometry system will provide a more detailed view of lightning activity, thereby aiding in the climate change prediction that could impact electricity generation from renewable sources. Accurate lightning location detection can also serve as a basis for designing effective lightning protection systems for renewable energy infrastructure.